Zasadnicze motywy podejmowania działalności gospodarczej w Polsce przez inwestorów zagranicznych - Polak, Waldemar (Undertaking Economic Activity in Poland By Foreign Investors, 2008)
Foreign capital inflow to Poland is a priority because it conditions fast development of the Polish economy. One should focus on creating a favourable investment climate for foreign investors in Poland. The conditions for investors should be clear and based on lasting lawful regulations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 441-450